Research progress on alternative kombucha substrate transformation and the resulting active components - Su, Jingqian; Tan, Qingqing; Tang, Qian; Tong, Zhiyong; Yang, Minhe (Frontiers in Microbiology, 2023)
Kombucha is a customary tea-based beverage that is produced through the process of fermenting a mixture of tea and sugar water with symbiotic culture of bacteria and yeast (SCOBY). Traditional kombucha has various beneficial effects and can improve immunity. The significant market share of Kombucha can be attributed to the growing consumer inclination towards healthy foods within the functional beverage industry. The research focus has recently expanded from the probiotics of traditional black tea kombucha to encompass other teas, Chinese herbs, plant materials, and alternative substrates. There is a lack of comprehensive literature reviews focusing on substance transformation, functional, active substances, and efficacy mechanisms of alternative kombucha substrates. This article aimed to bridge this gap by providing an in-depth review of the biological transformation pathways of kombucha metabolites and alternative substrates. The review offers valuable insights into kombucha research, including substance metabolism and transformation, efficacy, pharmacological mechanism, and the purification of active components, offering direction and focus for further studies in this field.